Constraints on free parameters of the simplest bilepton gauge model from the neutral kaon system mass difference - Pisano, F.; Silva-Sobrinho, J. A. [UNESP]; Tonasse, M. D. (My University, 1998)
We consider the contributions of the exotic quarks and gauge bosons to the mass difference between the short- and the long-lived neutral kaon states in the SU(3)CXSU(3)LXU(1)N model. The lower bound MZ∼ 14 TeV is obtained for the extra neutral gauge boson Z'0. Ranges for values of one of the exotic quark masses and quark mixing parameters are also presented. © 1998 The American Physical Society.